Electroconvulsive therapy induced gray matter increase is not necessarily correlated with clinical data in depressed patients - Sartorius, Alexander; Demirakça, Traute; Böhringer, Andreas; Clemm von Hohenberg, Christian; Aksay, Suna Su; Bumb, Jan Malte; Kranaster, Laura; Thomann, Philipp; Wolf, Robert Christian; Ende, Gabriele (Brain stimulation, 2019)
Background Electroconvulsive therapy (ECT) and depression have been associated with brain volume changes, especially in the hippocampus and the amygdala. Methods In this retrospective study we collected data from individual pre-post ECT whole brain magnetic resonance imaging scans of depressed patients from six German university hospitals. Gray matter volume (GMV) changes were quantified via voxel-based morphometry in a total sample of 92 patients with major depressive episodes (MDE). Additionally, 43 healthy controls were scanned twice within a similar time interval. Results Most prominently longitudinal GMV increases occurred in temporal lobe regions. Within specific region of interests we detected significant increases of GMV in the hippocampus and the amygdala. These results were more pronounced in the right hemisphere. Decreases in GMV were not observed. GMV changes did not correlate with psychopathology, age, gender or number of ECT sessions. We ruled out white matter reductions as a possible indirect cause of the detected GMV increase. Conclusion The present findings support the notion of hippocampus and amygdala modulation following an acute ECT series in patients with MDE. These results corroborate the hypothesis that ECT enables primarily unspecific and regionally dependent neuroplasticity effects to the brain.